Aging in the Commonwealth Caribbean - Serow, William J. (CARICOM Secretariat GeorgetownGY, 1997)
Considers the trends in population aging across the region and deals with the determinants in the trends of population aging. Analyzes the role which migration to, from, and within the region has played in trends in the number of older persons. Focuses on the social characteristics of the older population of the region and deals with their economic status. Looks at their housing and their self reported disability status. Highlights the demography of aging in Bermuda.